The Use of Murajaah Method in Improving Qur'an Memorization: Tahfiz A-Qur'an - Sari, Roza Muspita; Zou, Guijiao; Jie, Lie (International Journal of Educational Narratives, 2023)
Background. In this study, it discusses how the use of the muraja'ah method in improving the memorization of the Qur'an carried out at the house of tahfiz nurul yaqin jorong simpang nagari batagak sub-district sungai pua bukit tinggi. Purpose. This study aims to find out how a memorizer of the Qur'an to keep his memorization. That is by means of the muraja'ah method. Method. This type of research is qualitative, namely researchers directly researching tahfiz teachers at the tahfiz house. This research was conducted using qualitative methods, by conducting observations and interviews at the nurul yaqin tahfiz house, namely through ustazah hernita as a teacher at the tahfiz house. Results. How to keep the Qur'an is by the muraja'ah method, which muraja'ah method is a way for a memorizer of the Qur'an to repeat his memorization in a predetermined way so that the memorization does not forget or even disappear. Conclusion. The muraja'ah method carried out in the tahfiz house is quite good, because the teacher teaches muraja'ah by applying it before each study or ziyadah together, namely by doing a relay which will make it easier for tahfiz students to repeat their memorization.